Pengaruh Current Ratio, Debt To Equity Ratio, Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Ridwan Fahmi Asas; Nuril Fauzan Akbaruddin (Jurnal Ekonomi dan Bisnis Digital, 2024)
A good company is a company that has good values ​​in it and will automatically be viewed favorably by investors which will have a positive influence on the continuity of the company. This research aims to determine the current ratio, debt to equity ratio, return of assets and company growth towards company value in the sub-sector of metal mining and similar companies listed on the Indonesia Stock Exchange for the period 2016 - 2020. This research data is secondary data. The data collection technique for this research is purposive sampling technique. The population in this research was 15 companies, and the sample used in this research was 13 companies. The analysis method used is panel data regression using the econometric program View 10 (Eviews10). The results of this research show that the current ratio has an insignificant effect on company value, the debt to equity ratio has a positive and significant effect on company value, return on assets has an insignificant effect on company value, and company growth has a positive and significant effect on company value.